C1: Giải phương trình: a) x+2/x-2 – 5/x = 8/x^2-2x b) 2x(x-3) = x-3

Photo of author

By Rose

C1: Giải phương trình:
a) x+2/x-2 – 5/x = 8/x^2-2x
b) 2x(x-3) = x-3

0 bình luận về “C1: Giải phương trình: a) x+2/x-2 – 5/x = 8/x^2-2x b) 2x(x-3) = x-3”

  1. Đáp án+Giải thích các bước giải:

    `a)ĐKXĐ:x\ne 0;x\ne 2`

    `\frac{x+2}{x-2}-5/x=\frac{8}{x^2-2x}`

    `<=>\frac{x(x+2)}{x(x-2)}-\frac{5(x-2)}{x(x-2)}=\frac{8}{x(x-2)}`

    `=>x(x+2)-5(x-2)=8`

    `<=>x^2+2x-5x+10=8`

    `<=>x^2-3x+10-8=0`

    `<=>x^2-3x+2=0`

    `<=>x^2-x-2x+2=0`

    `<=>x(x-1)-2(x-1)=0`

    `<=>(x-1)(x-2)=0`

    `<=>x-1=0`

     hoặc `x-2=0`

    `<=>x=1(tm)` hoặc `x=2(ktm)`

     Vậy `S=\{1\}`

    `b)2x(x-3)=x-3`

    `<=>2x(x-3)-(x-3)=0`

    `<=>(x-3)(2x-1)=0`

    `<=>x-3=0`

     hoặc `2x-1=0`

    `<=>x=3` hoặc `x=1/2`

     Vậy `S=\{3;1/2\}`

  2. Đáp án + Giải thích các bước giải:

    `a//(x+2)/(x-2)-(5)/(x)=(8)/(x^{2}-2x)` `(ĐKXĐ:x\ne{2;0})`

    `<=>(x(x+2))/(x(x-2))-(5(x-2))/(x(x-2))=(8)/(x(x-2))`

    `<=>x(x+2)-5(x-2)=8`

    `<=>x^{2}+2x-5x+10=8`

    `<=>x^{2}-3x+2=0`

    `<=>(x^{2}-2x)-(x-2)=0`

    `<=>x(x-2)-(x-2)=0`

    `<=>(x-2)(x-1)=0`

    `⇔` \(\left[ \begin{array}{l}x-2=0\\x-1=0\end{array} \right.\) 

    `⇔` \(\left[ \begin{array}{l}x=2(KTM)\\x=1(TM)\end{array} \right.\) 

    Vậy `S={1}`

    `b//2x(x-3)=x-3`

    `<=>2x(x-3)-(x-3)=0`

    `<=>(x-3)(2x-1)=0`

    `⇔` \(\left[ \begin{array}{l}x-3=0\\2x-1=0\end{array} \right.\) 

    `⇔` \(\left[ \begin{array}{l}x=3\\x=\dfrac{1}{2}\end{array} \right.\) 

    Vậy `S={3;(1)/(2)}`

Viết một bình luận